Self-perceptions of communicative competence: exploring self-views among first year students in a Mexican university - López González, María Dolores (2010)
This research assessed students’ self-perception of communicative competence in EFL in a Mexican university. I argued there was a gap in the knowledge available in the field at the tertiary education level in Mexico that needed filling because of the impact that self-perception has on individuals’ decisions to act, in this case, to engage in communication acts in the foreign language. The objectives guiding my research were: first, to address the information gap; second, to test the scale created for this study (CCQ); and third, to explore influences on students’ self-perceptions in this context.